Effects of therapeutic interventions on mental health of women experiencing domestic violence in Tehran, Iran - Arzani, Parand (2012)
This study was carried out to investigate the effects of three therapeutic interventions on the mental health of women who are experiencing domestic violence. The therapeutic interventions investigated in this study are Cognitive-behaviour therapy, Feminist therapy, and Combination of therapies (CBT & FEM). The research design was experimental using both descriptive and inferential statistics to address the research objectives and hypotheses, respectively. Sixty women from a counselling center in Tehran, who are experiencing domestic violence, were randomly assigned into treatment groups based on systematic random sampling. Potential respondents were initially screened by using the Domestic Violence Questionnaire (Ghahari, 2004). Later on respondents were selected based on the following criteria: age, marital status, duration of marriage and number of marriage. An interpersonal interview was carried out and the SCL-90-R was administered as pre-test. The subjects were then placed in the following groups: a) Cognitive-behaviour Therapy, b) Feminist Therapy, c)Combination of Therapies (Cognitive-behaviour therapy and Feminist therapy), and d) Control Group. The SCL-90-R was administered at the last session as post-test. All the respondents participated in eleven individual therapy sessions, whereby every session lasted for 50 minutes. In the process of the study, seven respondents dropped out. A paired sample t-test was employed to compare the differences in pre-test and post-test scores of each treatment group. The analysis of variance, One-Way ANOVA was also used to determine the differences between groups. The study indicated that the Combination of Therapies (Cognitive-behaviour therapy and Feminist therapy) is the most effective approach in treating the mental health of women. The results showed that all treatments were effective in the following order:Combination of Therapies (Cognitive-behaviour therapy and Feminist therapy), Feminist Therapy, and Cognitive-behaviour Therapy. The implications of the study include: 1) the combination of therapies enabled the counsellors to open up the women’s awareness regarding their social rights and equal opportunities through cognitive restructuring, 2) CBT and Feminist therapy are two approaches which can be integrated by counsellors in Iran who are working with victimized women, 3) counsellor educators can consider the inclusion of feminist theory in the curriculum of guidance and counselling at universities, 4) counsellors should recognize the need to explore gender equality issues in the treatment of women’s mental health problems, 5) policy makers can encourage mental health care centres to use this knowledge in treating victimized women. This research provides a foundation for family researchers to undertake further studies on the dynamism and factors that enable families to cope with and survive the challenges of domestic violence, to employ Feminist therapy in combination with CBT in other cultures, and to identify the factors that characterized functional and successful families.